Analisis Yuridis Pembentukan Badan Pengelola Investasi Daya Anagata Nusantara (BPI Danantara) - Vina Hardyana Infantri; Retno Meilani (Pusat Riset dan Inovasi Nasional, 2025)
The third amendment to Law Number 1 of 2025 on State-Owned Enterprises has presented several juridical issues that need to be studied in depth, one of which is related to the establishment of the Daya Anagata Nusantara Investment Management Agency (Danantara). One of the main issues is the lack of public participation in drafting regulations, both at the planning stage and the formulation of legal norms. In addition, the existence of Danantara, which adopts the Sovereign Wealth Fund (SWF) model, raises the potential for overlap with a similar institution, the Indonesia Investment Authority (INA), which was established earlier. Provisions regarding the filling of organ positions, exceptions to the definition of state finances and losses, and weak external oversight mechanisms further strengthen concerns about irregularities in governance. These conditions are potentially at odds with the general principles of good governance (AAUPB), the Law on Government Administration, the Law on State Ministries, and the Law on the Eradication of Corruption. Therefore, it is necessary to analyze the establishment of the Daya Anagata Nusantara Investment Management Agency (Danantara), focusing on the legal basis for its establishment and its compatibility with the principles of constitutional law and government administration in Indonesia.